The Status of Chinese National Theoretical Discourse System and Its Correlation With Psychological Education of College Students - Xiang, Yueting; Miao, Yurong; Zhang, Jianxiang; Lin, Yujia (Frontiers in Psychology, 2021)
In recent years, in the face of new situations and problems in society, the discourse system, academic concepts and related research perspectives of Chinese national theory have been strongly impacted by Western thought, making the discourse mode of western national theory become the second discourse system outside the traditional Chinese national theory. In order to further promote the construction of Chinese national discourse system in college students' mental health education system, the study first starts with the concept of national theory and discourse system, and then uses the literature method to consult the development status of Chinese national theoretical discourse system and college students' mental health education. The results show that students' grade is directly proportional to students' satisfaction with mental health education, that is, with the increase of grade, students are more and more satisfied with mental health education. The attendance rates of college students, high school students, junior middle school students and primary school students are about 98%, 87%, 81% and 78%, respectively. In addition, students who are willing to actively accept psychological education account for about 38% of the total number of students, those who do not refuse account for 51% of the total number of students, and those who are unwilling to accept account for 11% of the total number of students. Among these students, their acceptance of mental health education will not be affected by other factors. Besides, college students' satisfaction score with mental health education is about 4.1, high school students' satisfaction score is about 3.6, junior middle school students' satisfaction score is about 2.9, and primary school students' satisfaction score is about 2.1. It reveals that the degree of satisfaction with mental health education is also related to grade. While taking mental health education courses, students not only realize a comprehensive understanding of the theory of the Chinese nation, but also greatly improve their national self-confidence and psychological quality. Moreover, it also strengthened disseminating the theoretical discourse of the Chinese nation. Therefore, the exploration is of great significance to the development of Chinese national theoretical discourse system in college students' psychological education.